Softening of the flux line lattice in Ge/Pb multilayers - Neerinck, D. (1992)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Katholieke Universiteit Leuven; Bélgica